2014
DOI: 10.1074/jbc.m113.531970
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glucose Metabolism and Glycerolipid Formation by Fatty Acids and GPR40 Receptor Signaling Underlies the Fatty Acid Potentiation of Insulin Secretion

Abstract: Background: Pathways underlying fatty acid potentiation of glucose-stimulated insulin secretion have not been fully elucidated.Results: In INS-1 cells, fatty acids increase de novo production of glycerolipids and simultaneously increase glucose utilization. GPR40 receptor activation increases these activities. Conclusion: Fatty acids enhance the production of multiple signals supporting glucose-stimulated insulin secretion. Significance: The studies clarify the effects of fatty acids and GPR40 activity in ␤ ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 42 publications
(69 reference statements)
1
57
0
Order By: Relevance
“…The free, unbound, fatty acid concentration under these conditions is only ϳ10 -20 nM (105,442). While the need for albumin binding is generally appreciated in the literature, molar ratios of 6:1 or even higher have been employed in vitro (144,285,332,472), producing unbound fatty acid concentrations close to 1 M, or 100 times higher than the normal physiological range (FIGURE 8A). One concern in such studies is the possibility that excessive fatty acid exposure in vitro may produce artifactual changes in metabolism, for example, due to nonspecific mitochondrial uncoupling (269,277), that might mask a physiologically relevant positive signaling or bioenergetic effect.…”
Section: E Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free, unbound, fatty acid concentration under these conditions is only ϳ10 -20 nM (105,442). While the need for albumin binding is generally appreciated in the literature, molar ratios of 6:1 or even higher have been employed in vitro (144,285,332,472), producing unbound fatty acid concentrations close to 1 M, or 100 times higher than the normal physiological range (FIGURE 8A). One concern in such studies is the possibility that excessive fatty acid exposure in vitro may produce artifactual changes in metabolism, for example, due to nonspecific mitochondrial uncoupling (269,277), that might mask a physiologically relevant positive signaling or bioenergetic effect.…”
Section: E Fatty Acidsmentioning
confidence: 99%
“…Schnell et al (472) observed oleate-induced oscillations and a sustained increase in [Ca 2ϩ ] c in primary mouse ␤-cells in the presence of 5 mM glucose; however, a molar ratio of 6:1 seemed to be required. El-Azzouny et al (144) performed an exhaustive study of the bioenergetic and metabolic consequences of acute fatty acid exposure of INS-1 cells, including the use of a GPR40 antagonist, but again used a high 6:1 molar ratio. Ferdaoussi et al (152) compared islets from wild-type and Gpr40Ϫ/Ϫ mice, concluding that GPR40 was responsible for ϳ50% of the oleatemediated enhancement of second phase secretion (FIGURE 8B), but utilized a 5:1 molar ratio.…”
Section: Gpr40/ffa1mentioning
confidence: 99%
“…Studies using MIN6 and INS-1 insulin-producing cell lines have shown increases in insulin secretion induced by longchain FAs through GPR40 receptor activity [9,14]. Increase in insulin secretion was also observed in isolated mice pancreatic islets treated with polyunsaturated linoleic and α-linolenic acids [15].…”
Section: Introductionmentioning
confidence: 80%
“…Although the effects of FAs on pancreatic β-cell functions [3,11,[14][15][16][17][18][19][20] have been well documented, the molecular consequences of FA deficiency on pancreatic β-cell function remain to be clarified. Some studies have already reported the relationship of specific nutrient deficiencies with posterior high risk of diabetes and hyperglycemia 22-24, however; only few of them approach the cellular mechanisms of β-cell response to the deficiency conditions 25.…”
Section: Introductionmentioning
confidence: 99%
“…Free fatty acids such as palmitate potentiate glucose-stimulated insulin secretion by altering b cell metabolism (El-Azzouny et al 2014). Islets from PWD mice secreted significantly more insulin in response to palmitate than B6 islets (Fig.…”
Section: Increased Glucose-stimulated Insulin Secretion From Pwd Isletsmentioning
confidence: 98%